Phylogeographical relationships of Sicilian brown trout and the effects of genetic introgression on morphospace occupation. (5th June 2014) - Fruciano, Carmelo; Pappalardo, Anna Maria; Tigano, Concetta; Ferrito, Venera
<x xml:space="preserve">Abstract</x> Genetic introgression of aquaculture stocks in local forms is well documented in many fish species but their evolutionary consequences for the local populations have not been thoroughly explored. Due to its wide geographical range, the existence of many locally adapted forms and the frequent occurrence of introgression of aquaculture stocks in local forms, brown trout represents the ideal system to study the effects of such introgressions. Here, we focus on a group of rivers and streams in Sicily (Italy), and, by using molecular tools, we show that autochthonous populations are probably derived from the Southern Atlantic clade, which is present in the Iberian peninsula and North Africa. Three out of the four studied rivers reveal signs of genetic introgression of domestic stocks. Finally, by using advanced geometric morphometric analyses, we show that genetic introgression produces a higher degree of morphological variability relative to that observed in non‐introgressed populations. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 112, 387–398.